TANGGUNG JAWAB TRIDHARMA PERGURUAN TINGGI MENJAWAB KEBUTUHAN MASYARAKAT - Bukman Lian (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Universities carry out the function of tridharma: education and teaching, research, and community service. The three dharma are interrelated, among others, the first dharma (education: theoretical) and second (research: innovation) must concretely support the third dharma (devotion: transformation). The research was conducted not only for the sake of the research itself, credit numbers, promotion, money. In carrying out the research contained an important mission, namely for the benefit of society. That is, the community remains a focus, especially in social research. So, the results and findings of the research must have a "back-flow" to the community. Research must be followed up with community service that is in the interests of the community. Research must have a positive impact on society; the community is not just a respondent. Types of research vary: basic, development, survey, exploration, applicative, and others. Not all results and research findings can be followed up with community service. However, there are also a number of results of research that can be continued to the community service action. Research to produce findings that have empirical truth values can be accounted for. If this is community service, the quality of the community service will also increase, meaning that the impact on the target audience is more efficient. Universities donations to the community through community service are also more significant. Universities is no longer exclusive: untouched and unwilling to touch and the community feels closer and has a universities.